Nilai Budaya Tradisional Kesenian Gendang Beleq: Studi Etnografi Komunikasi Masyarakat Desa Wanasaba Nusa Tenggara Barat - Lalu Muhammad Robby Hakiki; Vani Dias Adiprabowo (Faculty of Languages and Arts, Universitas Negeri Padang, 2023)
This study discusses the preservation of Gendang Beleq art in Wanasaba Village, East Lombok. Gendang Beleq is a traditional musik art form of the Sasak ethnic group that holds significant cultural value and is used in various traditional ceremonies. However, this art form faces challenges in the age of technology and the younger generation's interest in modern musik. The research employs a qualitative ethnographic communication method with the research location in Wanasaba Village. Data is collected through observation, interviews, and documentation. The research findings indicate that Gendang Beleq has essential artistic, historical, communal, and educational values within Lombok culture. This art form enhances culture, preserves cultural heritage, unites the community, and provides skills and cultural understanding to the younger generation. Despite the challenges, Gendang Beleq continues to evolve with the influence of time. This research provides a deeper understanding of the importance of preserving and developing Gendang Beleq art as a valuable cultural heritage. Preservation efforts enrich local culture and enhance appreciation for traditional arts in society.